2016
DOI: 10.1016/j.jvs.2016.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Versus Longitudinal Incisions for the Exposure of the Femoral Artery in Treating Patients With Peripheral Vascular Disease

Abstract: Methods: A consecutive 123 patients who survived proximal AAD surgery were reviewed at a single institution. The medical charts and computed tomography (CT) studies of these patients were reviewed from 2005 to 2014. The short axis area of the true lumen (TL), the false lumen (FL), and the total cross-sectional area were measured from reconstructed images using centerline technique at the largest segment each of the aortic arch, descending thoracic aorta (TA), aorta proximal to the celiac artery, and abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The rate of wound complications after groin incision for femoral endarterectomy and lower extremity revascularization is reported to be as high as 30 to 40% in vascular surgery patients. [7][8][9] Wound complications including infection, lymphoceles, and dehiscence are associated with prolonged hospital length of stay (LOS) and higher resource utilization. 9 More recently, total percutaneous technique without surgical incisions is being increasingly used in EVAR.…”
mentioning
confidence: 99%
“…The rate of wound complications after groin incision for femoral endarterectomy and lower extremity revascularization is reported to be as high as 30 to 40% in vascular surgery patients. [7][8][9] Wound complications including infection, lymphoceles, and dehiscence are associated with prolonged hospital length of stay (LOS) and higher resource utilization. 9 More recently, total percutaneous technique without surgical incisions is being increasingly used in EVAR.…”
mentioning
confidence: 99%
“…Seven studies were included, which involved a total of 5922 groin incisions (1951 longitudinal, 3971 transverse) in 5659 patients (Table 1). 3,7,9–13 Five studies were case‐controlled studies, 7,9,10,12,13 and two studies were randomized controlled trials 3,11 . Six studies were performed in a single institution, 3,7,10–13 whereas a single study reviewed outcomes from the Vascular Quality Initiative (VQI) database 9 .…”
Section: Resultsmentioning
confidence: 99%
“… 3,7,9–13 Five studies were case‐controlled studies, 7,9,10,12,13 and two studies were randomized controlled trials 3,11 . Six studies were performed in a single institution, 3,7,10–13 whereas a single study reviewed outcomes from the Vascular Quality Initiative (VQI) database 9 . The VQI database contains demographic, clinical, procedural and outcome data from a wide range of vascular procedures performed in multiple centres in the USA and Canada 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of lymphatic channels during vascular surgery and failure of subsequent healing may result in persistent leakage, presenting as lymphocele or lymphocutaneous fistula, and may occur in as many as 18% of arterial interventions [6]. A variety of factors have also been identified that may predispose patients to lymphatic leak including surgical procedure and graft type, incision techniques, as well as patient demographics [3,5,7]. As a result, patients who develop postvascular dissection lymphatic leak have delayed wound healing, are at greater risk of infection and graft rejection, and spend more time in the hospital, thereby increasing the cost of care [2,5,6].…”
Section: Introductionmentioning
confidence: 99%